Thermally induced crystallization, hole-transport, NLO and photovoltaic activity of a bis-diarylamine-based push-pull molecule - Yue Jiang (Nature Portfolio, 2017)
Abstract The synthesis of a molecule constituted of two diarylamine-based push-pull chromophores covalently linked via their nitrogen atom is described. Comparison of the electronic properties with the parent monomer shows that dimerization has negligible influence on the electronic properties of the molecule but exerts a dramatic impact on the capacity of the material to self-reorganize. Application of thermal annealing to thin films induces the crystallization under original morphologies, a process accompanied by a partial bleaching of the absorption in the visible range and by a huge increase of hole-mobility. X-ray diffraction data on single crystals reveal the presence of π-stacked organization with a non-centrosymmetric co-facial arrangement of the dipoles which leads to intrinsic 2nd order bulk NLO properties of thin films as evidenced by second harmonic generation under 800 nm laser light. The implications of this thermally induced crystallization on the photovoltaic properties of the material are discussed on the basis of preliminary results obtained on simple bilayer organic solar cells.